2000
DOI: 10.1073/pnas.140218797
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the role of the Golgi complex and lipid rafts in biosynthetic transport of cholesterol to the cell surface

Abstract: In this study, we compared the transport of newly synthesized cholesterol with that of influenza virus hemagglutinin (HA) from the endoplasmic reticulum to the plasma membrane. The arrival of cholesterol on the cell surface was monitored by cyclodextrin removal, and HA transport was monitored by surface trypsinization and endoglycosidase H digestion. We found that disassembly of the Golgi complex by brefeldin A treatment resulted in partial inhibition of cholesterol transport while completely blocking HA trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
193
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(212 citation statements)
references
References 48 publications
(42 reference statements)
12
193
0
Order By: Relevance
“…We have previously shown that extensive fenestration of the Golgi cisternae takes place in FEN-treated leek seedlings (Hartmann et al, 2002). These changes in the morphology of the Golgi may affect the steady state of membrane flux between GA and PM, emphasizing the key role played by this organelle in the transport of newly synthesized sterols to the cell surface of plant cells, as in animal cells (Heino et al, 2000). In higher eukaryotes, sterols and sphingolipids are gradually enriched along the secretory pathway (van Meer and Sprong, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…We have previously shown that extensive fenestration of the Golgi cisternae takes place in FEN-treated leek seedlings (Hartmann et al, 2002). These changes in the morphology of the Golgi may affect the steady state of membrane flux between GA and PM, emphasizing the key role played by this organelle in the transport of newly synthesized sterols to the cell surface of plant cells, as in animal cells (Heino et al, 2000). In higher eukaryotes, sterols and sphingolipids are gradually enriched along the secretory pathway (van Meer and Sprong, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…Both vesicular and nonvesicular lipid transport mediate intracellular lipid trafficking from the ER. Yet, inhibition of vesicular transport by pharmacological and genetic manipulations such as BFA or colchicine treatment, ATP depletion, and specific sec mutants (such as Sec18 mutant) has no effect on intracellular transport of certain lipid species (Kaplan and Simoni 1985b;Urbani and Simoni 1990;Heino et al 2000;Baumann et al 2005). Furthermore, imaging and biochemical studies using fluorescent lipid analogs, such as DHE (dehydroergosterol; a fluorescent cholesterol analog) and radioactive labels lipids, respectively, support the involvement of nonvesicular transport in intracellular lipid trafficking (Maxfield and Mondal 2006).…”
Section: Nonvesicular Lipid Transportmentioning
confidence: 99%
“…The transport of sterols from the ER is unaffected by drugs or genetic mutations that block vesicular transport, and is thought to be mediated mainly by spontaneous lipid transfer and by certain LTPs (Urbani and Simoni 1990;Heino et al 2000;Maxfield and Wustner 2002;Baumann et al 2005). Although sterols are highly hydrophobic lipids their spontaneous movement between certain membranes could be very rapid (a half-time of 1 min or less) (Dawidowicz 1987), and can thereby support substantial sterol transport between specific membranes.…”
Section: Lipid Transport From the Ermentioning
confidence: 99%
“…The role of membrane rafts in the assembly and budding of enveloped viruses has been investigated for influenza virus [59,63,[150][151][152][153][154][155][156][157][158][159][160], HIV-1 [63,[161][162][163][164][165][166][167][168][169][170][171][172][173], HTLV-1 [174], measles virus (Paramyxoviridae) [63,175,176], Sendai virus [Paramyxoviridae] [177,178], Newcastle disease virus (NDV; Paramyxoviridae) [179,180], RSV [147,148,[181][182][183][184], HSV [185,186], murine cytomegalovirus (MCMV; Herpesviridae) [187], Ebola virus [70,188], Marburg virus [70], and vesicular stomatitis virus (VSV; Rhabdoviridae) …”
Section: Role Of Membrane Rafts In Virus Genome Replication Assemblymentioning
confidence: 99%
“…HA, NA, NP and M2 independently utilize membrane rafts together with apical targeting signal sequence for the apical sorting process, leading to efficient preferential budding and release of progeny viruses from the apical surface membrane. However, direct interactions with membrane rafts are not necessarily essential for apical sorting of these viral proteins, indicating that they can also interact with apical sorting machineries outside their membrane rafts [150,[152][153][154]156]. For example, cellular protein VIP17/MAL, a raftassociated protein, is involved in apical transport of HA in dog kidney MDCK cells [192].…”
Section: Role Of Membrane Rafts In Virus Genome Replication Assemblymentioning
confidence: 99%